Moral and Spiritual Perspectives in the Semantic Study of the Poem Da’il Ayyama Taf’alu Ma Tasya‘u by Imam Asy-Syafi’i - Hajar, Hendar Ibnu; Hadi, Mardi; Firdaus, Abdul Gofar; Asrofi, Imam (UIN Siber Syekh Nurjati, 2025)
Research is a study of the elements that form poetry. In analyzing poetry, attention is usually paid to the relationship between lyrics in verses, the relationship between verses, intrinsic elements in verses, and the message conveyed by a poet, and includes the style of language used and the meaning contained in a poem. This study aims to analyze the aspects of lexical semantics and grammatical semantics in the poem by Imam Asy-Syafi'i entitled